2022
DOI: 10.3390/ijms23147810
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Inhibit the Response of Pancreatic Ductal Adenocarcinoma Cells to Gemcitabine and TRAIL Treatment

Abstract: Pancreatic ductal adenocarcinoma remains an aggressive cancer with a low 5-year survival rate. Although gemcitabine has been a standard treatment for advanced pancreatic cancer, patients often develop resistance to this therapeutic. We have previously shown that treating pancreatic cancer cells in vitro with a combination of gemcitabine and the cytokine TRAIL significantly reduced both cell viability and survival. The data presented here demonstrate that this response to treatment is inhibited when cells are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Interestingly, in our validation, the treatment of HNSCC cells with this known inhibitor of EV biosynthesis did not significantly affect cell viability or cell morphology, but it enhanced the antitumor effect of CDDP, which in turn led to a clear decrease in ATP7B expression (Figures 4 and 5). Rimmer et al reported that the antitumor effect of gemcitabine on pancreatic cancer cells was enhanced under a GW4869 combination 60 . Others have reported that the combination of GW4869 and doxorubicin against acute myeloid leukemia similarly enhanced sensitivity to chemotherapy 51 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in our validation, the treatment of HNSCC cells with this known inhibitor of EV biosynthesis did not significantly affect cell viability or cell morphology, but it enhanced the antitumor effect of CDDP, which in turn led to a clear decrease in ATP7B expression (Figures 4 and 5). Rimmer et al reported that the antitumor effect of gemcitabine on pancreatic cancer cells was enhanced under a GW4869 combination 60 . Others have reported that the combination of GW4869 and doxorubicin against acute myeloid leukemia similarly enhanced sensitivity to chemotherapy 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Rimmer et al reported that the antitumor effect of gemcitabine on pancreatic cancer cells was enhanced under a GW4869 combination. 60 Others have reported that the combination of GW4869 and doxorubicin against acute myeloid leukemia similarly enhanced sensitivity to chemotherapy. 51 Abad et al revealed a new mechanism of acquired chemotherapy resistance in triple negative breast cancer (TNBC) cells, in which EVs transport mitochondria to susceptible cancer cells and enhance their resistance to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the buffer was discarded to fill the plate with 2.0 ml of fresh media. The dish was then moved to the incubator for 24 h or 48 h before detaching and suspending the cells to count them manually and assess cell viability with the Trypan Blue exclusion assay (see subsection C of the Supplementary Information) [23,58,59]. See figure 4 for a graphical depiction of the plate management.…”
Section: Magnetic Fluid Hyperthermiamentioning
confidence: 99%